Gradle fundamentals : from basic syntax to plugins, repositories, dependencies, and multi-project builds - Kousen, Kenneth A.; Safari eBooks ([Place of publication not identified] : O'Reilly Media, 2015)
"Learn how to implement Gradle, the Groovy-based build automation system that can help you build and test software projects, from small to large. In this video course, Java consultant Ken Kousen demonstrates Groovy's relationship to Java, and takes a close look at POGOs--plain old Groovy objects--and how they define properties, access modifiers, and generate methods. You'll learn all of the Groovy mechanisms in a simple, non-trivial application. This video provides detailed Gradle examples, including the Spock testing framework, an overview of the Gradle builds for the Spring framework, and the default Gradle build for Android projects. In this video course, you'll explore: Java project builds, Groovy project builds, custom tasks, conditional task execution, multi-project builds, miscellaneous features, plugins."--Resource description page.
Title from title screen (viewed October 2, 2015).
Presenter, Ken Kousen.
Keywords: Gradle (Computer file); Groovy (Computer program language); Computer software -- Development; Electronic books